Tingkat kebugaran fisik dan status berat badan pada anak-anak dan remaja: Perbandingan antara siswa kota Surabaya dan Kabupaten Sidoarjo - Wiriawan, Oce (Universitas Nusantara PGRI Kediri, 2022)
Obesity, a sedentary lifestyle, and poor cardiorespiratory fitness in childhood can be bad for children especially regarding physical fitness and increased weight. This study aimed to analyze and compare the physical fitness and weight status of children and adolescents in Surabaya and Sidoarjo regency. This research uses a survey approach using physical fitness tests and weight measurements. The research instrument on physical fitness uses a physical fitness test with 5 items test. While the weight status is measured by measuring the body mass index (BMI). The sample selection of research subjects used random sampling techniques. The results showed that the physical fitness boys' students in The city of Surabaya and Sidoarjo regency are the same in the moderate category. In contrast, girls in the city of Surabaya are better compared to Sidoarjo regency. The teenage boys and girls of Surabaya city are better than the adolescent boys and girls students of the Sidoarjo regency. The weight status of Surabaya city boys is better compared to Sidoarjo regency boys. In contrast, the girls of Surabaya and Sidoarjo are included in the average category. The teenage boys of Surabaya city are better than the adolescent students of the Sidoarjo regency, in the teenage students of Surabaya city are better than the female adolescent students of the Sidoarjo regency. This research can be used as data on the development of students, teachers, and all related parties that must correctly stabilize the condition of students, children, and adolescents to carry out their activities.